Inhibitor selectivity between aldo–keto reductase superfamily members AKR1B10 and AKR1B1: Role of Trp112 (Trp111). Issue 22 (4th October 2013) - Zhang, Liping; Zhang, Hong; Zhao, Yining; Li, Zhe; Chen, Shangke; Zhai, Jing; Chen, Yunyun; Xie, Wei; Wang, Zhong; Li, Qing; Zheng, Xuehua; Hu, Xiaopeng
Abstract : The antineoplastic target aldo–keto reductase family member 1B10 (AKR1B10) and the critical polyol pathway enzyme aldose reductase (AKR1B1) share high structural similarity. Crystal structures reported here reveal a surprising Trp112 native conformation stabilized by a specific Gln114‐centered hydrogen bond network in the AKR1B10 holoenzyme, and suggest that AKR1B1 inhibitors could retain their binding affinities toward AKR1B10 by inducing Trp112 flip to result in an "AKR1B1‐like" active site in AKR1B10, while selective AKR1B10 inhibitors can take advantage of the broader active site of AKR1B10 provided by the native Trp112 side‐chain orientation. Abstract : Crystal structures of AKR1B10 holoenzyme. Trp112 side‐chain flipping in AKR1B10 explains non‐selectivity of AKR1B1 inhibitors. Native Trp112 side‐chain orientation is critical for selective AKR1B10 inhibitors.